Pengaruh Brand Image, Program Gratis Ongkir dan Variasi Produk terhadap Keputusan Pembelian Produk Wardah Everyday BB Cream di Marketplace Shopee - Alma Khairani; Novita Wahyu Setyawati; Fransiscus Dwikotjo Sri Sumantyo (Fibonacci: Jurnal Ilmu Ekonomi, Manajemen dan Keuangan, 2025)
This study aims to determine the effect of brand image (X1), free shipping program (X2), and product variety (X3) on purchasing decisions for Wardah Everyday BB Cream products on the Shopee marketplace. The research method used in this study is quantitative. The sampling technique used to take samples in this study was non-probability sampling. The researcher used a purposive sampling technique. The population in this study were all students of the Management Department of the University of Bhayangkara Jakarta Raya in 2021. The sample in this study consisted of 114 respondents obtained by distributing questionnaires via Google Form. Data analysis used multiple linear analysis with the help of SPSS version 25. The population in this study were all students of the Management Department of the University of Bhayangkara Jakarta Raya in 2021. The sample in this study amounted to 114 respondents obtained by distributing questionnaires via Google Form. Data analysis used multiple linear analysis with the help of SPSS version 25. The results showed that the Brand Image variable had a positive and significant effect on Purchasing Decisions. The Free Shipping Program variable has a positive and significant effect on Purchasing Decisions and the Product Variation variable has a positive and significant effect on Purchasing Decisions. Then that there is a positive and significant influence between the independent variables in the form of Brand Image, Free Shipping Program, and Product Variation on Purchasing Decisions simultaneously.